The Urgency of Motivation to Seek Knowledge (Analysis of the Prophet's Hadiths About Education) - Robitul Abror; Ahmad Mohammad Tidjani (Values: Jurnal Kajian Islam Multidisiplin, 2024)
Motivation plays an important role in seeking knowledge in Islam. This study examines the concept of motivation in Islamic teachings, especially in educational contexts, through the analysis of relevant hadiths. In Islamic teachings, motivation is referred to as "al niiyat" or intention, and every action depends on the intention behind it. Educational motivation is defined as the conscious intention or desire of an adult or educator to guide the physical and spiritual development of students towards the formation of a personality that is balanced with science. These hadiths emphasize that if someone seeks knowledge with good intentions, Allah will make his path to heaven easier. Seeking knowledge that is beneficial for oneself and fellow humans is beneficial both in this world and in the afterlife. Islam strongly recommends learning, and these hadiths are the main driving force in seeking knowledge. The study confirms that if a person tries and learns sincerely, Allah will appreciate his efforts and provide an understanding of His knowledge. These hadiths also confirm the position of people with knowledge is higher than that of people without knowledge, with the promise of a high degree of honor and degree for those who combine knowledge with good deeds. This study emphasizes the importance of motivation in Islamic education and the spiritual and worldly benefits of seeking knowledge with pure intentions.